2014
DOI: 10.5586/aa.2014.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ability of fifteen onion (Allium cepa L.) cultivars to accumulate nitrates

Abstract: <p>The aim of a two-year study was to characterise selected <em>Allium cepa </em>L. genotypes with regard to their ability to accumulate nitrates in bulbs as well as to search for a possible relation between NO<sub>3</sub><sup>-</sup> concentration and dry matter content. Fifteen cultivars of edible onion, mostly of long-day genotype with different growing periods, bulb size and skin colour, were taken for the experiment. Seeds of particular cultivars were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…'Red Baron' treated with Maximus Amino Protect. The obtained values were higher than those reported by Majkowska-Gadomska et al (2016), and comparable with those reported by Tendaj et al (2014) and Wojciechowska and Kołton (2014) which ranged from 112 to 207 g depending on the cultivar. Explanations as in Table 1 Following the trend of the weight results, onions of cv.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…'Red Baron' treated with Maximus Amino Protect. The obtained values were higher than those reported by Majkowska-Gadomska et al (2016), and comparable with those reported by Tendaj et al (2014) and Wojciechowska and Kołton (2014) which ranged from 112 to 207 g depending on the cultivar. Explanations as in Table 1 Following the trend of the weight results, onions of cv.…”
Section: Resultssupporting
confidence: 86%
“…Different results were reported by Badałek et al (2016) -25.5 to 27.3 mg N-NO -3 kg -1 fresh weight. In a study by Wojciechowska and Kołton (2014), nitrate (V) levels in common onions ranged from 73.4 mg N-NO -3 kg -1 fresh weight for cv. 'Efekt' to 118.6 mg N-NO -3 kg -1 fresh weight for cv.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive N accumulation in plant tissues is attributed to the imbalance between uptake and assimilation (Cárdenas-Navarro et al, 1999). As a result, the uptake of nitrate may reduce osmatic pressure that limits the storage of organic solutes in vacuole (Wojciechowska and Kołton, 2014).…”
Section: Discussionmentioning
confidence: 99%